Variability in nitrogen stable isotope ratios of macroalgae: consequences for the identification of nitrogen sources. Issue 1 (1st December 2014) - Ochoa‐Izaguirre, María Julia; Soto‐Jiménez, Martín F.; Dunton, K.
<x xml:space="preserve">Abstract</x> In our research, we collected and analyzed numerous macroalgal specimens (738) for isotopic analysis sampled over a year at monthly intervals across 20 sites within the Urías lagoon complex, a typical subtropical coastal ecosystem located in the Gulf of California. We quantified and characterized (chemically and isotopically) the N loads received by Urías throughout a year. We studied the spatial‐temporal variation of the chemical forms and isotopic signals of the available N in the water column, and we monitored in situ different environmental variables and other hydrodynamic parameters. Multiple N sources (e.g., atmospheric, sewage, seafood processing, agriculture and aquaculture effluents) and biogeochemical reactions related to the N cycle (e.g., ammonia volatilization, nitrification and denitrification) co‐occurring across the ecosystem, result in a mixture of chemical species and isotopic compositions of available N in the water column. Increased variability was observed in the δ15N values of macroalgae (0.41‰–22.67‰). Based on our results, the variation in δ15N was best explained by spatio‐temporal changes in available N and not necessarily related to the N sources. The variability was also explained by the differences in macroalgal biology among functional groups, species and/or individuals. Although the δ15N‐macroalgae technique was a useful tool to identify N sources, its application in coastal ecosystems receiving multiple N sources, with changing environmental conditions influencing biogeochemical processes, and high diversity of ephemeral macroalgal species, could be less sensitive and have less predictive power.